2012
DOI: 10.1001/archsurg.2012.496
|View full text |Cite
|
Sign up to set email alerts
|

Perioperative Risk Assessment in Robotic General Surgery

Abstract: Eight hundred eightyfour consecutive patients who underwent a robotic procedure in our institution between April 2007 and July 2010. Main Outcomes Measures: Perioperative morbidity and mortality.Results: During the study period, 884 patients underwent a robotic procedure. The conversion rate was 2%, the mortality rate was 0.5%, and the overall postoperative morbidity rate was 16.7%. The reoperation rate was 2.4%. Mean length of stay was 4.5 days (range, 0.2-113 days). In univariate analysis, several factors we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(9 citation statements)
references
References 46 publications
0
8
0
1
Order By: Relevance
“…Likely it is the extent of tissue plane manipulation or dissection, whether open or robotic, that plays a greater role in the surgical footprint as is echoed in prior literature. 10,15 EBL as a factor contributing to increased high grade complications is logical, as many times these patients require considerable intraoperative blood products and fluid resuscitation leading to ICU level care due to longer times weaning ventilation and other secondary issues such as pre-renal acute kidney injury. However, it is unclear if EBL is merely a predictor of the complexity of the operation and may reflect unaccounted for variables such as tumor complexity or perirenal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…Likely it is the extent of tissue plane manipulation or dissection, whether open or robotic, that plays a greater role in the surgical footprint as is echoed in prior literature. 10,15 EBL as a factor contributing to increased high grade complications is logical, as many times these patients require considerable intraoperative blood products and fluid resuscitation leading to ICU level care due to longer times weaning ventilation and other secondary issues such as pre-renal acute kidney injury. However, it is unclear if EBL is merely a predictor of the complexity of the operation and may reflect unaccounted for variables such as tumor complexity or perirenal fibrosis.…”
Section: Discussionmentioning
confidence: 99%
“…For robotic liver/bile duct procedures, the incidence of complications was 26.1%, mortality rate was 3.2%, and conversion rate was 7.6%, which were all above the overall mean values of robotic procedures[19]. Buchs et al[20] analyzed 884 cases of robotic surgery performed at the University of Illinois Hospital between April 2007 and June 2010 and found that hepatectomy was considered as an advanced robotic procedure, and multivariate analysis showed that advanced procedure was a factor significantly associated with a higher risk for complications.…”
Section: Introductionmentioning
confidence: 99%
“…Desde principios de la década de 2000, se ha informado que la cirugía robótica es factible y segura, incluso para procedimientos avanzados y complejos. 4,5 En 2003, Intuitive Surgical (Sunnyvale, CA) se fusionó con Computer Motion (Goleta, CA) creando de manera efectiva un único proveedor robótico. Desde entonces, ha habido avances tecnológicos sustanciales en la plataforma quirúrgica Da Vinci ® destinada principalmente a mejorar la eficiencia operativa.…”
Section: Introductionunclassified